2021
DOI: 10.3390/ijerph182010740
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Low-Carbohydrate High-Fat Diet Combined with High-Intensity Interval Training on Body Composition and Maximal Oxygen Uptake: A Systematic Review and Meta-Analysis

Abstract: The low-carbohydrate high-fat (LCHF) diet has recently been subject to attention on account of its reported influences on body composition and physical performance. However, the combined effect of LCHF with high-intensity interval training (HIIT) is unclear. A systematic review and meta-analysis were conducted to explore the effect of the LCHF diet combined with HIIT on human body composition (i.e., body weight (BM), body mass index (BMI), fat mass (FM), body fat percentage (BFP), fat-free mass (FFM)) and maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
1
4
0
1
Order By: Relevance
“…Therefore, we attribute the significant increase of relative VO 2peak (ml/kg/min) values in the VLCHF and VLCHF+HIIT groups rather to the rapid body mass reduction than any enhancement of aerobic capacity per se. Although carbohydrate restricted diets combined with HIIT were shown to enhance aerobic capacity in various populations (54) as well as in the obese (55), this rapid body mass reduction effect on relative VO 2peak values is not usually considered (56). The walking HIIT protocol and/or 12 week intervention period were probably not sufficient enough to increase aerobic capacity in the present study, although the volume of exercise at high intensity was significantly increased in both HIIT and VLCHF+HIIT groups.…”
Section: Cardiorespiratory Fitness Levelmentioning
confidence: 54%
“…Therefore, we attribute the significant increase of relative VO 2peak (ml/kg/min) values in the VLCHF and VLCHF+HIIT groups rather to the rapid body mass reduction than any enhancement of aerobic capacity per se. Although carbohydrate restricted diets combined with HIIT were shown to enhance aerobic capacity in various populations (54) as well as in the obese (55), this rapid body mass reduction effect on relative VO 2peak values is not usually considered (56). The walking HIIT protocol and/or 12 week intervention period were probably not sufficient enough to increase aerobic capacity in the present study, although the volume of exercise at high intensity was significantly increased in both HIIT and VLCHF+HIIT groups.…”
Section: Cardiorespiratory Fitness Levelmentioning
confidence: 54%
“…In contrast, the same diet was found to be an effective strategy for reducing excess body fat in men and women with overfat constitution ( 6 ). Systematic reviews and meta-analyses show also beneficial effects of low carbohydrate diets combined with exercise on body composition, triglycerides, and aerobic capacity in adults with obesity ( 17 , 18 ). Consuming a high fat diet, especially one with high saturated fatty acids (SFA), is thought to impair key aspects of cardiometabolic health.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis has shown that a low-carbohydrate high-fat diet combined with HIIT reduces body weight and fat mass, while maintaining lean body mass and enhancing aerobic capacity. Moreover, another recent systematic review and meta-analysis has shown that patients who adhere to a low-carbohydrate diet for six months can experience remission of diabetes without adverse consequences [ 62 ]; however, these studies did not included inflammatory biomarker analyses [ 63 ]. In the papers selected for this systematic review, only one of the studies showed the effects a HIIT training that four different types of diets have on patients with T2D [ 55 ].…”
Section: Discussionmentioning
confidence: 99%